Risk Management in Redesigning Main Dam for the Tiu Suntuk Dam Implementation - Aisyah Nur Amalina Lestari; Endah Kurniyaningrum; Silia Yuslim (Green Publisher Indonesia, 2026)
The redesign of the Tiu Spara Dam main dam was carried out in response to changes in technical conditions and operational needs of the project, but this process has the potential to pose various risks that can affect the stability, safety, and performance of the dam. This study aims to identify risk indicators, analyze risk levels and priorities, and formulate risk control strategies in the redesign of the Tiu Suntuk Dam main dam. The method used is a descriptive quantitative approach based on ISO 31000:2018 risk management, with data collection through field observations, interviews, literature studies, and questionnaire dissemination to experienced respondents. Risk analysis was conducted using the Severity Index method to assess the probability and impact of the risk, which was subsequently mapped into a risk matrix. The results showed that the highest risk came from the technical aspects, namely changes in soil carrying capacity, availability of materials for new designs, and suitability of dam design with actual slope conditions, all of which fall under the category of extreme risk. Therefore, it is necessary to strengthen technical investigations, design adjustments, improve work quality control, and implement systematic and integrated risk management. This research is expected to be a reference in risk management in similar dam projects to improve structural safety and the sustainability of dam functions.